The role of vision in control of orientation in a back tuck somersault - Davlin, C. D.; Sands, W. A.; Shultz, B. B. (Motor control, 2001)
During a back tuck somersault, the angular velocity of the head is thought to surpass the visual system's ability to maintain a distinct and continuous picture of the environment. The primary objectives of this research were to determine if differences existed with regard to trunk and lower body kinematics, as well as landing balance, when gymnasts perform back tuck somersaults under different vision conditions. Ten female gymnasts (age = 11.6 +/- 2.67 years, competitive level = 8 +/- 1.15, and training time in gymnastics = 5.9 +/- 1.63 years) performed back tuck somersaults under 4 vision conditions while wearing electromagnetic sensors that allowed automatic digitizing. Although no significant differences were found between vision conditions with regard to timing, joint angles, and joint angular velocities, gymnasts were more stable at landing under conditions that allowed vision during either the entire somersault or the last half of the sumersault.